IL-7 treatment supports CD8+ mucosa-associated invariant T-cell restoration in HIV-1-infected patients on antiretroviral therapy. (27th March 2018) - Sortino, Ornella; Richards, Elizabeth; Dias, Joana; Leeansyah, Edwin; Sandberg, Johan K.; Sereti, Irini
Abstract : N/A: Chronic HIV-1 infection is associated with lower frequencies and functional impairment of mucosa-associated invariant T (MAIT) cells. We evaluated IL-7 treatment to restore MAIT cells in peripheral blood of chronically HIV-1-infected individuals on antiretroviral therapy. IL-7 led to increased relative and absolute levels of MAIT cells, and this expansion occurred primarily in the CD8 + subset. These results suggest that IL-7 may represent a therapeutic intervention for the restoration of MAIT cells in chronic HIV-1 infection.